Visualisasi Budaya Lokal Melalui Ilustrasi Dua Dimensi Puti Bungsu Bapakaian Cawek Koto Nan Gadang - Audria Gustrisia; Sahrul N; Asril; Chintiya Larashati (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
In the midst of modernization, the younger generation's interest in local culture, including Minangkabau traditional clothing, especially in the Koto Nan Gadang area, is decreasing. This condition encourages the need for a creative approach to revive the values ​​and philosophical meanings inherent in Koto Nan Gadang traditional clothing, one of which is through the design of two-dimensional illustrations as a visual medium that is close to today's generation. This study aims to design a two-dimensional illustration of the youngest daughter (unmarried woman) wearing traditional clothing typical of the Koto Nan Gadang area in West Sumatra as a visualization of local culture through digital illustrations. The design method used is the Five Phases of Design Graphic Process method designed by Robin Landa. The method consists of 5 stages, namely orientation, analysis, concept, design, and implementation. Data collection was carried out qualitatively obtained from observations and interviews, as well as from books or archives related to the research object. This design produces a female character wearing traditional clothing typical of Koto Nan Gadang which is visualized in a two-dimensional illustration style, so that it can be a documentation and visual interpretation of traditional clothing of West Sumatra, especially in Koto Nan Gandang. This work not only functions as a medium for art appreciation, but also as an educational tool in introducing the cultural identity of Koto Nan Gadang to a wider audience, especially the younger generation who are familiar with digital media